2018
DOI: 10.1039/c8cc00856f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of chiral oxazolines from unactivated ketones and isocyanoacetate esters by synergistic silver/organocatalysis

Abstract: A multicatalytic approach that combines a bifunctional Brønsted base-squaramide organocatalyst and Ag as Lewis acid has been applied in the reaction of unactivated ketones with tert-butyl isocyanoacetate to give chiral oxazolines bearing a quaternary stereocenter. The formal [3+2] cycloaddition provided high yields of the corresponding cis-oxazolines with good diastereoselectivity and excellent enantioselectivity, being applied to aryl-alkyl and alkyl-alkyl ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…London dispersion interactions between sterically demanding DTBM P‐substituents and the aromatic ring of the aldehyde may also contribute to the stereoselectivity. These mechanistic features are in accord with the hydrogen‐bonding mechanism proposed for the silver/squaramide‐based organocatalyst hybrid system, [3o,p] and might encourage the reconsideration of proposed mechanisms of other catalyst systems for isocyanoacetate aldol reactions [3] and related metal/organocatalyst hybrid systems [2b,11] . Further catalyst and reaction development based on the information obtained in this study is underway.…”
Section: Methodssupporting
confidence: 79%
“…London dispersion interactions between sterically demanding DTBM P‐substituents and the aromatic ring of the aldehyde may also contribute to the stereoselectivity. These mechanistic features are in accord with the hydrogen‐bonding mechanism proposed for the silver/squaramide‐based organocatalyst hybrid system, [3o,p] and might encourage the reconsideration of proposed mechanisms of other catalyst systems for isocyanoacetate aldol reactions [3] and related metal/organocatalyst hybrid systems [2b,11] . Further catalyst and reaction development based on the information obtained in this study is underway.…”
Section: Methodssupporting
confidence: 79%
“…After extensive optimization, they found that the combination of a bifunctional Brønsted base‐squaramide 17 b (5 mol %) with Ag 2 O (2.5 mol %) effectively promoted the reaction of various aryl‐alkyl and alkyl‐alkyl ketones with isocyanoacetates 1 , forming a range of cis ‐4‐carboxyl‐2‐oxazolines 21 in high yields with moderate to good excellent diastereoselectivities and excellent enantioselectivities (Scheme 5 c). [33] The result of this method contrasted with that described by Dixon and co‐workers, who obtained the trans ‐oxazolines 21 as the major product. Therefore, these two methods are complementary to each other.…”
Section: [3+2] Cycloaddition Reactions Of Isocyanides With Polarized mentioning
confidence: 59%
“…The same research group also showed the application of Ag + /squaramide cooperative catalysis in (3 + 2) annulation between isocyanoacetate 260 and simple ketones 326 in course of preparing chiral oxazolines 327 bearing two contiguous stereocenters. [133] Several acetophenone derivatives containing both electron donating and withdrawing substituents in the aryl ring reacted with different alkyl isocyano acetates to deliver the products with high chemical yields, poor to excellent cis/ trans selectivities and excellent enantiocontrol for both diastereoisomers. Diastereoselectivity increases markedly with increase in steric bulk of the alkyl substituent in the ketone and only few examples were presented involving alkyl, alkyl ketones (Scheme 87a).…”
Section: Synthesis Of Heterocycles Containing N and Omentioning
confidence: 99%